Recent Advances in the Clinical Application of Adrenal Vein Sampling - Zhong, Shan; Zhang, Tianyue; He, Minzhi; Yu, Hanxiao; Liu, Zhenjie; Li, Zhongyi; Song, Xiaoxiao; Xu, Xiaohong (Frontiers in Endocrinology, 2022)
We reviewed clinical research investigating the applications of adrenal vein sampling (AVS). AVS could be applied not only to primary aldosteronism (PA) but also to other endocrine diseases, such as adrenocorticotropic hormone (ACTH) independent Cushing syndrome (AICS) and hyperandrogenemia (HA). However, the AVS protocol requires improvements to increase its success rate. Using the computed tomography image fusion, coaxial guidewire technique, and fast intraprocedural cortisol testing (CCF) technique could improve the success rate of catheterization in AVS for PA. ACTH loading could be considered in medical centers with a low selectivity of AVS for PA but is not essential in those with mature AVS technology. The continuous infusion method should be recommended for ACTH stimulation in AVS for PA to reduce adverse events. AVS has not been routinely recommended before management decisions in AICS, but several studies verified that AVS was useful in finding out the source of excess cortisol, especially for distinguishing unilateral from bilateral disease. However, it is necessary to reassess the results of AVS in AICS with the use of reference hormones to fully normalize cortisol levels. In addition, it is essential to determine the optimal model that combines AVS results and mass size to guide the selection of surgical plans, including identifying the dominant gland and presenting the option of staged adrenalectomy, to minimize the impact of bilateral resection. For HA, AVS combined with ovarian intravenous sampling to locate excess androgens could be considered when imaging results are equivocal.